Temsirolimus with or without Megestrol Acetate and Tamoxifen for Endometrial Cancer: a Gynecologic Oncology Group Study - Fleming, Gini F. (2014)
BACKGROUND: Preclinical evidence suggested that blockade of the PI3K/AKT/mTOR pathway might overcome resistance to hormonal therapy. METHODS: We performed a randomized phase II trial of intravenous temsirolimus 25 mg weekly versus the combination of weekly temsirolimus with a regimen of megestrol acetate 80 mg bid for three weeks alternating with tamoxifen 20 mg bid for three weeks in women with recurrent or metastatic endometrial carcinoma. RESULTS: There were 71 eligible patients who received at least one dose of therapy with 21 of these treated on the combination arm which was closed early because of an excess of venous thrombosis, with 5 episodes of deep venous thrombosis (DVT)and 2 pulmonary emboli. There were three responses observed in that arm (14%). A total 50 eligible patients were treated on the single agent arm with 3 episodes of DVT and 11 responses (22%). Response rates were similar in patients with prior chemotherapy (7 of 29; 24%) and those with no prior chemotherapy (4 of 21; 19%). Two of four patients with clear cell carcinoma responded. CONCLUSIONS: Adding the combination of megestrol acetate and tamoxifen to temsirolimus therapy did not enhance activity and the combination was associated with an excess of venous thrombosis. Temsirolimus activity was preserved in patients with prior adjuvant chemotherapy. These findings will have implications for future trial design.